2012
DOI: 10.1111/boc.201100062
|View full text |Cite
|
Sign up to set email alerts
|

Rab11 is phosphorylated by classical and novel protein kinase C isoenzymes upon sustained phorbol ester activation

Abstract: This report shows for the first time that Rab11 is differentially phosphorylated by distinct PKC isoenzymes and that this post-translational modification might be a regulatory mechanism of intracellular trafficking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…While blots using unpurified lysates from cells not induced with PMA revealed no visible band corresponding to phosphorylated Rabphilin 3A ( Figure 7A). This result suggests that PRKC proteins possibly target Rab effectors proteins, which is consistent with previous studies showing different Rab proteins as targets for PRKC isozymes [88,[90][91][92]. Further work will be necessary to characterize this possible functional link of phosphorylated Rabphilin 3a and exocytosis, however, the western blot is consistent with a role of PRKC in regulated exocytosis in MCF-7 cells.…”
Section: Pma-supporting
confidence: 89%
“…While blots using unpurified lysates from cells not induced with PMA revealed no visible band corresponding to phosphorylated Rabphilin 3A ( Figure 7A). This result suggests that PRKC proteins possibly target Rab effectors proteins, which is consistent with previous studies showing different Rab proteins as targets for PRKC isozymes [88,[90][91][92]. Further work will be necessary to characterize this possible functional link of phosphorylated Rabphilin 3a and exocytosis, however, the western blot is consistent with a role of PRKC in regulated exocytosis in MCF-7 cells.…”
Section: Pma-supporting
confidence: 89%
“…2007). Interestingly, a recent study demonstrated that Rab11 can be phosphorylated and activated by PKC (Pavarotti et al . 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Rab11 is required for bile canalicular formation in WIF‐B9 cells, regulates canalicular localization of BSEP, and mediates TUDC‐ and cAMP‐induced translocation of MRP2 to the PM . Because Rab11 activation involves PKC‐mediated phosphorylation, and cAMP and TUDC activate nPKCδ and cPKCα, respectively, it can be speculated that phosphorylation (and activation) of Rab11 by cPKCα and nPKCδ may be involved in MRP2 translocation to the PM. Further studies are needed to establish a role for Rab11 phosphorylation by PKCs in MRP2 translocation.…”
Section: Beyond Pkc Isoformsmentioning
confidence: 99%